(untitled) (Quinto Sol, 2013)
This paper is an enquiry into the strategies for Access to land displayed by the Russo family, rural producers who, by the end of the nineteenth Century settled as cattle tenants on southern areas of the Territorio Nacional de La Pampa. Through the analysis of sources belonging to the prívate archive of the family and other public documents, we reconstructed differents moments in the life of the Russos, marked by the strategies carried through to economically settle themselves and maximize opportunities by combining tenancy-property, stability factors and the scale of tenancy, in diverse areas for two generations. This case study, focused upon the family and located in a zone with characteristics that differ from those sketched in the bulk of dominant historiography, allows to shed light on issues concerning the access to land by pampean rural producers at the end of the nineteenth Century and the first decade of the twentieth, and thus, discuss some traditional postulates, besides from establishing the existence of regional variations.